2018
DOI: 10.18203/2320-1770.ijrcog20180176
|View full text |Cite
|
Sign up to set email alerts
|

PPIUCD: awareness and reasons for non-acceptance

Abstract: Background: The recommended interval between pregnancies is at least 24 months in order to reduce the risk of adverse maternal, perinatal and infant outcomes. Ministry of Health & Family Welfare, Government of India has taken initiative for provision of IUCD in immediate postpartum period. Several training programs and awareness camps are conducted by NHM for health service providers and also for the public.  The aim of the study was to determine proportion of women accepting post placental intrauterine Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Alukal et al also stated similar finding with 74.1% acceptance in women having unplanned pregnancy. 18 This indicates that women who had unplanned pregnancies either due to non-use of contraception or due to previously failed contraception are more motivated for PPIUCD insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Alukal et al also stated similar finding with 74.1% acceptance in women having unplanned pregnancy. 18 This indicates that women who had unplanned pregnancies either due to non-use of contraception or due to previously failed contraception are more motivated for PPIUCD insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have recorded rates as low as 8% to as high as 50%. [14][15][16][17][18] A low acceptance rate (8.2%) has been recorded by Prabha et al 14 In a study conducted by Kachan Rani, 15 high rate (51.6%) of acceptance of PPIUCD was found. An acceptance rate ranging between 43.8 -50% has been mentioned in a research work done by Rajuan Doley et al 18 The rate (24.36%) of PPIUCD insertion recorded in our study lies midway between above mentioned studies.…”
Section: Discussionmentioning
confidence: 91%
“…An acceptance rate ranging between 43.8 -50% has been mentioned in a research work done by Rajuan Doley et al 18 The rate (24.36%) of PPIUCD insertion recorded in our study lies midway between above mentioned studies. [15][16][17][18][19] The difference in rate of insertion is due to multiple factors operating in different setups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored reasons for low acceptance of the PPIUCD. [6][7][8] Several of these are common irrespective of the demographical differences. One of the most common reasons authors found for non-acceptance of PPIUCD was general apprehension which accounted for a whopping 29% (almost one third) of reasons for refusal.…”
Section: Discussionmentioning
confidence: 99%